Phagocytic activity of neutrophils improves over the course of therapy of diabetic foot infections - (:unkn) unknown (W B SAUNDERS CO LTD, 2007)
Aims: The aim of this study was to investigate changes in phagocytic activity of neutrophils of type 2 diabetic patients with foot infections over short treatment courses. The potential utility of the phagocytic index in determining the efficacy of treatment modalities and it's relationship with metabolic control parameters were evaluated. Methods: The phagocytic activity of neutrophils was determined in blood samples of 38 type 2 diabetic patients with foot infections (14 women and 24 men). Mean age and mean duration of diabetes were 66.3 +/- 9.4 and 19.1 +/- 11.2 (yrs), respectively. All patients received standard treatment (intensive insulin therapy, antibiotherapy, hyperbaric oxygen therapy and surgical debridement). Phagocytic activity of neutrophils was determined by a standard method. Phagocytic activity of neutrophils, acute phase proteins (C-reactive protein) and glycosylated haemoglobin was determined before therapy and two weeks later. Results: The phagocytic index before and after therapy were 47.7 +/- 11.4 and 62.5 +/- 15.6, respectively (p < 0.05). There was a significant correlation between phagocytic index and both CRP and HbA1c (r = 0.52, p < 0.05 and r = -0.41, p < 0.05, respectively). Conclusions: Derangement of carbohydrate metabolism may underlie the impairment of bactericidal activity of neutrophils of poorly controlled diabetic patients. These data reveal that phagocytic activity improves during short-course standard therapy and might enable monitoring of efficacy of treatment modalities in diabetic: patients with foot infections. (C) 2007 The British Infection Society. Published by Elsevier Ltd. All rights reserved.
Keywords: neutrophil phagocytic index; treatment efficacy; diabetic foot infections; COLONY-STIMULATING FACTOR; GLUCOSE CONTROL; OXIDATIVE BURST; IN-VITRO; MELLITUS; DYSFUNCTIONS; ASSOCIATION; MANAGEMENT; ULCERS